Pulsatile Flow Measurement by a Speckle Triangle Assessment - Yuan, Yuan; Bi, Yong; Gao, Xiao Cao; Gao, Wei Nan (Frontiers in Physics, 2021)
The blood flow in the coronary artery (CA) is pulsatile and much higher than that measured in brain, retina, and skin before. Its quantitative measurement is medically significant in the coronary artery bypass grafting (CABG). Here we firstly, to the best of our knowledge, detect the pulsatile flow using Laser speckle contrast imaging technique. Since the factors influencing the flow rate in the CA are complex, we developed a comprehensive model, a speckle triangle assessment (STA), to assess the characteristics of the flow: speckle flow index (SFI), mean flow index (MFI) and pulsatility index (PI). The phantom experiment was performed and found that our customized setup possessed high dynamic range of the velocity measurement with good sensitivity. It also indicated that pulsatile flow estimated by the speckle triangle assessment are promising to obtain a more accurate assessment of a coronary artery’s patency in the CABG.